Cardinal Miguel Ángel Ayuso Guixot’s Dialogue Views Against Interreligious Dialogue In Indonesia - Dismas Kwirinus; Petrus Yuniarto; Kristianus Damianus Apo (Jayapangus Press, 2023)
This research focuses on Cardinal Miguel Ángel Ayuso Guixot’s Dialogue Views on Interreligious Dialogue in Indonesia. According to Cardinal Ayuso, this research aims to understand the importance of inter-religious dialogue in Indonesia. Dialogue between religious adherents is indeed being warmly encouraged by the Church to build a just and prosperous society. This research uses descriptive qualitative methods and critical reading of the text. Based on a critical reading of this research text, it is analyzed and combined with materials related to Cardinal Ayuso’s dialogue views in Das Dikasterium fur den Interreligiosen Dialog, the Church’s teachings on the dialogue between religions, especially those contained in the documents of the Second Vatican Council and documents -Documents after the Second Vatican Council and scientific works related to religious life and authentic fraternity. The findings in this study are that the concept of inter-religious dialogue in Cardinal Ayuso’s perspective is more focused on the “existential attitude” that every human being must have in his life to promote peace in the world. The initial step for inter-religious dialogue must be preceded by theological dialogue. Then the dialogue must be followed up at a practical level in the form of inter-religious cooperation to solve humanitarian and national issues jointly.